D.C conductivity of In2O3: SnO2 thin films and manufacturing of gas sensor - Hasan, Bushra A. (Iraqi Journal of Physics, 2018)
Compounds were prepared from In2O3 doped SnO2 with different doping ratio by mixing and sintering at 1000oC. Pulsed Laser Deposition PLD was used to deposit thin films of different doping ratio In2O3: SnO2 (0, 1, 3, 5, 7 and 9 % wt.) on glass and p-type wafer Si(111) substrates at ambient temperature under vacuum of 10-3 bar thickness of ~100nm. X-ray diffraction and atomic force microscopy were used to examine the structural type, grain size and morphology of the prepared thin films. The results show the structures of thin films was also polycrystalline, and the predominate peaks are identical with standard cards ITO. On the other side the prepared thin films declared a reduction of degree of crystallinity with the increase of doping ratio. Atomic Force Microscopy (AFM) measurements show the average grain size exhibit to change in non-systematic manner with the increase of doping ratio with tin oxide. The average grain size increases at doping ratios 1, 5 and 7 % from 52.48 to 79.12, 87.57, and 105.59 nm respectively and decreases at residual doping ratio. The average surface roughness increases from 0.458 to 26.8 nm with the increase of doping ratio. The gas sensing measurements of In2O3:SnO2 thin films prepared on p-Si to NO2 gas showed good sensitivity and Maximum sensitivity (50) obtained for In2O3:SnO2 prepared on p-Si at operating temperature 573 K and doping ratio 7 % and 9 %. Maximum speed of response time (8 sec) at operating temperature 573 K and doping ratio 1 %.